Uma sequência didática investigativa sobre os mecanismos termorreguladores e adaptações a ambientes extremos - Darjana Vieira Santos Moraes (2022)
This work was conducted with the aim of improving the approach to teaching thermoregulation for high school students, bringing a scientific education proposal to integrate the content of the subjects taught as Natural Sciences. Thus, a didactic sequence was developed and applied that allowed students to use concepts learned in Chemistry, Physics, and Biology and their importance in maintaining the temperature in our body. In this way, it was expected that young people could understand that all subjects are important for the construction of knowledge: studying the properties of water, correlating heat and temperature through thermometry, understanding the transformation of chemical energy into heat through the construction of a calorimeter and other experiments by which they could prove the processes of heat exchange, such as conduction, convection, and irradiation. The students demonstrated that heat is exchanged between bodies with different temperatures. Moreover, by learning about the temperature of distinct groups of vertebrates and their adaptations to extreme environments, they realized that body temperature depends on the heat exchanged with the environment and that thermoregulation happens due to the existence of physiological mechanisms that control the flow of heat coupled to cellular metabolism. The theme allowed us to work on the contents of Natural Sciences and Their Technologies, keeping the focus on teaching Biology in an interdisciplinary way. The activities of the didactic sequence aroused the interest of the students, who engaged themselves to carrying out the experiments, in an original and creative way, demonstrating that they can go far beyond expectations when properly stimulated.